REGIONAL UNIVERSITY FALLS OUT OF EDUCATION DEVELOPMENT IN RUSSIA - Khazhismel G. Tkhagapsoyev (Высшее образование в России)
The article analyzes the problems of development of a regional university in modern Russia. One of the main problems is underestimation of the role of universities in solving social-economic and cultural-technological tasks within the region. It has been proposed to introduce the practice of a “Head University” status referring to the subsequent creation on this basis of regional scientific-educational clusters.